High hardness alloy nanometer nickel electroplating process

CN122879791APending Publication Date: 2026-10-09SHENZHEN YUSHENGPIN PRECISION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611242826.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0003]本发明的目的是解决现有铜件镀镍镀层硬度不足、高硬度替代方案成本高、产线改造投入大的问题,提供一种高硬度合金纳米镍电镀工艺,依托现有产线搭配纳米添加剂镀液,制得高硬度且兼具韧性的镍镀层,实现低成本环保量产

Benefits of technology

[0003]本发明的目的是解决现有铜件镀镍镀层硬度不足、高硬度替代方案成本高、产线改造投入大的问题,提供一种高硬度合金纳米镍电镀工艺,依托现有产线搭配纳米添加剂镀液,制得高硬度且兼具韧性的镍镀层,实现低成本环保量产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879791A_ABST
    Figure CN122879791A_ABST
Patent Text Reader

Abstract

The application provides a high-hardness alloy nano nickel electroplating process, which is suitable for red copper and purple copper workpiece processing and comprises the following steps: sequentially performing ultrasonic oil removal, multistage countercurrent water washing, anode electrolytic oil removal, hydrochloric acid activation, copper polishing, acid oil removal, sulfuric acid activation treatment on the workpiece, and then adopting a special nano nickel plating solution to complete alloy nano nickel electroplating under the conditions of constant temperature and constant pressure and full-cycle filtration, and finally obtaining a finished workpiece after plating layer protection, multistage water washing and drying. The application removes oil stains and oxide layers on the surface of the workpiece through fine segmented pretreatment, and cooperates with a nano composite plating solution system, so that a high-hardness and low-defect nickel plating layer can be stably prepared, the hardness and bending toughness of the plating layer are effectively balanced, the wear resistance of an AI server copper accessory is improved, the process is suitable for existing conventional electroplating production lines, and the production cost is low and the mass production stability is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal surface treatment technology, and more specifically, relates to a high-hardness alloy nano-nickel electroplating process. Background Technology

[0002] High-hardness nickel plating is widely used in copper and red copper conductive components of AI servers. As a silver-plated underlayer, it ensures the wear resistance and conductivity of the product during insertion and removal, and is a core surface treatment process for server connectors. However, the nickel plating prepared by the traditional conventional ammonia nickel electroplating process has a hardness of only 230~300HV, and its wear resistance is weak, which cannot meet the requirement of 20,000 insertion and removal wear resistance. Although the electroless nickel plating process that has replaced the industry has achieved the required plating hardness, its production cost increases by more than 50%, its production efficiency is low, its energy consumption is high, its wastewater treatment is difficult, and it requires additional space and special equipment to build an independent production line. It cannot be directly used for mass production on existing electroplating production lines, and it is difficult to balance the plating hardness, production cost and mass production conditions. Summary of the Invention

[0003] The purpose of this invention is to solve the problems of insufficient hardness of existing nickel plating layers on copper parts, high cost of high-hardness alternatives, and large investment in production line transformation. It provides a high-hardness alloy nano-nickel electroplating process that uses existing production lines and nano-additive plating solutions to produce a nickel plating layer with high hardness and toughness, achieving low-cost and environmentally friendly mass production.

[0004] The purpose and effect of the high-hardness alloy nano-nickel electroplating process of the present invention are achieved by the following specific technical means: A high-hardness alloy nano-nickel electroplating process, suitable for processing red copper / purple copper workpieces, includes the following steps: S1. Ultrasonic degreasing: Place the workpiece in a degreasing solution at 50~60℃ and ultrasonically treat it for 10~15 minutes. S2. Multi-stage counter-current water washing: The workpiece is rinsed using a multi-stage counter-current clean water method; S3, Anodic Electrolytic Degreasing: Electrolytic degreasing at a controlled temperature of 50~60℃ for 3~5 minutes, followed by S2 multi-stage countercurrent water washing; S4. Hydrochloric acid activation impregnation: Immerse the workpiece in hydrochloric acid with a mass fraction of 15%~25% for 1~2 minutes, and then perform S2 multi-stage countercurrent water washing. S5. Copper polishing treatment, followed by S2 multi-stage counter-current water washing. S6, Acidic Degreasing: Treat the workpiece with an acidic degreasing solution at 40~50℃ for 1~2 minutes, and then perform S2 multi-stage countercurrent water washing. S7. Sulfuric acid activation: Immerse the workpiece in 5%~10% sulfuric acid for 1~2 minutes, and then perform S2 multi-stage countercurrent water washing. S8, Alloy Nano Nickel Electroplating: Electroplating is performed using a special nano nickel plating solution. The temperature of the plating solution is controlled at 50~55℃, the pH value at 4.2~4.4, and the plating voltage at 3~5V. The plating solution is circulated and filtered throughout the electroplating process. After the electroplating is completed, S2 multi-stage countercurrent water washing is performed. S9. Coating protection treatment, followed by S2 multi-stage counter-current water washing after protection is completed; S10. Drying process to obtain the finished workpiece.

[0005] The electroplating process of this invention significantly improves the hardness of nickel plating by compounding a specific amount of nano-rare additives into a conventional nickel plating solution, combined with standardized segmented pretreatment, constant temperature and pressure electroplating, and a continuous circulation filtration system, without replacing existing electroplating production lines or adding new equipment and space. The hardness of the plating can be stably maintained at 470HV~520HV. At the same time, the hardness and bending flexibility of the plating can be balanced by adjusting the amount of nano-rare additives. Compared with traditional ordinary ammonia nickel plating, the wear resistance of the plating is significantly improved, which can meet the wear resistance requirements of AI server accessories for more than 20,000 insertion and removal cycles. Compared with electroless nickel plating, the production cost is reduced by more than 50%, the production efficiency is higher, the wastewater treatment is easier, and the environmental protection is stronger, enabling large-scale, high-efficiency, low-cost, and stable mass production.

[0006] The above technical solution can be further improved by the following measures: Furthermore, the special nano nickel plating solution contains the following components at the following concentrations: 80 g / L nickel ions, 20 g / L nickel chloride, 40 g / L boric acid, 100 ml / L comprehensive organic additives, and 5-10 g / L nano rare additives.

[0007] Furthermore, when the amount of nano-rare additives added is 5g / L, the Vickers hardness of the resulting nickel plating is stable at ≥470HV, and the workpiece can withstand 6 rounds of 90° bending without cracking; when the amount of nano-rare additives added is increased to 10g / L, the Vickers hardness of the plating can reach more than 500HV, and the number of rounds of 90° bending that the workpiece can withstand is reduced to 3.

[0008] Furthermore, a nickel plating layer with a thickness of 16 μm is obtained by electroplating in step S8, and the average Vickers hardness of the plating layer can reach 493.4 HV. When electroplating a 6 μm plating layer, the amount of nano rare additives is positively correlated with the hardness of the plating layer and negatively correlated with the flexibility of the plating layer.

[0009] Furthermore, in step S8, the electroplating process continuously operates the circulating filtration system to ensure that the nano-rare additives in the plating solution are evenly dispersed, thus preventing the nanoparticles from settling and agglomerating, which would cause uneven coating hardness.

[0010] Furthermore, after the hydrochloric acid activation and impregnation process in step S4 and the sulfuric acid activation process in step S7 are completed, at least two stages of countercurrent water washing process are set.

[0011] Furthermore, after copper polishing in step S5, a pure water spray rinsing process is added to remove polishing residue from the workpiece surface and prevent polishing impurities from contaminating the nano-nickel electroplating tank.

[0012] Furthermore, in step S9, the coating protection is achieved by immersion in a water-soluble nickel protective agent, followed by thorough rinsing with water. During the drying stage, the temperature is controlled at 60~80℃ to avoid high-temperature damage to the coating's hardness and toughness.

[0013] Furthermore, the nano-rare additives are made of nano-scale alloy rare powders with a particle size controlled between 10 and 100 nm. When these powders are combined with comprehensive organic additives, they can be uniformly dispersed in the plating solution system, simultaneously improving the hardness of the plating layer while retaining the bending toughness of the nickel layer. Attached Figure Description

[0014] Figure 1 This is a flowchart of the steps of a high-hardness alloy nano-nickel electroplating process according to the present invention; Figure 2 This invention relates to the relationship between the hardness of the material and the amount of nano-additives used. Figure 3 This invention relates to the relationship between the flexibility of the material and the amount of nano-additives used. Detailed Implementation

[0015] The embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples. The following examples are used to illustrate the technical solutions of the present invention, but should not be used to limit the scope of protection of the present invention.

[0016] Example:

[0017] like Figures 1 to 3 As shown, this invention provides a high-hardness alloy nano-nickel electroplating process, suitable for processing red copper / purple copper workpieces, comprising the following steps: S1. Ultrasonic degreasing: Place the workpiece in a degreasing solution at 50~60℃ and ultrasonically treat it for 10~15 minutes. After red and purple copper workpieces are cut, stamped, and bent, their surfaces retain residual stamping lubricating oil and mold rust-preventive oil. During transport and stacking, workshop dust adheres to the workpieces, and manual handling leaves behind a film of skin oils and sweat. These various contaminants continuously coat the metal substrate surface, forming an insulating layer. Subsequent electroplating of nickel metal can only adhere to the oily surface and cannot form a metal-to-metal bond with the copper substrate. During use, the nickel plating layer will peel off in large sections or areas due to insertion / extraction stress and temperature changes, losing its conductivity and wear-resistant protective properties.

[0018] Maintaining the degreasing solution temperature stably within the range of 50-60℃ reduces the viscosity of the grease, increasing the contact area between grease molecules and emulsifying and penetrating agents in the degreasing solution, thus improving the dissolution and emulsification rate of the grease. If the temperature is below 50℃, the viscosity of the grease is higher, and the emulsification and decomposition rate slows down. If the temperature is above 60℃, the evaporation rate of surfactants in the degreasing solution accelerates, and the consumption rate of reagents increases. When the ultrasonic equipment is working, it generates a large number of tiny cavitation bubbles inside the degreasing solution. The continuous generation and collapse of these bubbles generate a continuous impact force, repeatedly striking the workpiece's surface, holes, bends, and corners, peeling off solid grease particles embedded in the workpiece's microscopic depressions and crevices. The processing time is set to 10-15 minutes, which is suitable for server conductive copper parts with a standard thickness of 0.3-2mm. If the processing time is less than 10 minutes, a thin layer of oil will remain on the inside of the workpiece bends, the corners of holes and other shielded areas. If the processing time exceeds 15 minutes, it will not significantly improve the degreasing effect, but will only increase the consumption of electricity and degreasing agents, and lengthen the production cycle of a single batch of the entire electroplating production line.

[0019] S2. Multi-stage counter-current water washing: The workpiece is rinsed using a multi-stage counter-current clean water method; After a workpiece completes any of the chemical treatment processes such as degreasing, pickling, polishing, electroplating, or protection, the corresponding chemical solutions will be absorbed and retained inside the workpiece's planes, blind holes, gaps, and threaded structures. These solutions include various chemical components such as alkaline degreasing solutions, hydrochloric acid, sulfuric acid, polishing paste suspensions, nano nickel electroplating solutions, and water-soluble protective agents.

[0020] If the workpiece is transferred directly to the next process without rinsing, the residual chemicals carried by the workpiece will mix into the bath solution of the next process, continuously changing the solute concentration, acid-base balance, and additive content of the bath solution. This causes the bath solution performance to deteriorate continuously, requiring frequent replenishment of chemicals or even replacement of the entire bath, increasing production material costs. The multi-stage countercurrent cleaning system consists of at least two washing tanks connected in series. Clean water is continuously delivered to the last washing tank, and the water in the tank overflows forward in stages. The workpiece passes through the first, second, and finally the last washing tank from front to back, with the direction of workpiece movement opposite to the direction of water overflow.

[0021] The workpiece is first rinsed in a pre-stage water rinsing tank with a high residual concentration of chemicals to dilute the high concentration of chemicals on its surface. Then, it enters a final-stage water rinsing tank replenished with clean water to further reduce the amount of chemicals carried over to the surface. Compared to single-stage immersion rinsing, this cleaning method reduces the overall consumption of clean water. Through gradient dilution, it significantly reduces the total amount of chemicals carried to the next process by the workpiece, slowing down the degradation rate of the solutions in each main process, extending the stable service life of the solutions, and reducing the frequency of chemical replenishment and solution replacement. This rinsing step is set as a universal post-treatment unit for the entire electroplating process. Except for the drying process, after all other chemical treatment processes are completed, the workpiece needs to be transferred to this step for cleaning.

[0022] S3, Anodic Electrolytic Degreasing: Electrolytic degreasing at a controlled temperature of 50~60℃ for 3~5 minutes, followed by S2 multi-stage countercurrent water washing; Preliminary ultrasonic degreasing can only remove free liquid oil and loose dust adhering to the surface of the workpiece. However, the combined oxidized oil on the metal substrate surface of the workpiece, formed after high-temperature molding and storage oxidation, is tightly adhered to the copper substrate and cannot be completely removed by ultrasonic cavitation impact alone. The anodic electrolytic degreasing tank is equipped with a DC power supply, and the workpiece is connected to the circuit as the anode. After the power is turned on, the water molecules on the workpiece surface undergo an electrolytic reaction, continuously generating a large number of tiny oxygen bubbles.

[0023] Bubbles rise from the substrate surface to the water surface, generating pulling and scouring forces during their ascent, tearing and peeling away the oxide oil film layer tightly bonded to the copper substrate. Maintaining the electrolyte temperature at 50-60℃ enhances the molecular activity of emulsifying and saponifying agents within the electrolyte, accelerating the saponification and emulsification reaction rate of the oil stains and shortening the processing time required for oil stain removal. A processing time of 3-5 minutes is suitable for conventional red and purple copper workpieces with a thickness of 0.3-2mm; for workpieces with a substrate thickness greater than 2mm and a thick layer of oxide oil stains on the surface, a maximum processing time of 5 minutes can be used to ensure complete oil stain removal. After electrolytic treatment, the workpiece surface will carry highly alkaline electrolytic solution. The solution residue in the workpiece crevices will neutralize the acidic medium in the subsequent activation process, reducing the activation effect. Therefore, after all processes are completed, the workpiece needs to be transferred to an S2 multi-stage countercurrent water wash to gradually dilute and rinse away the alkaline solution residue adhering to the surface.

[0024] This can be achieved by replacing the DC power supply mode with a pulsed DC power supply mode, or by adding a pre-cleaning spray step before the anodic electrolytic degreasing process. Specifically: If replaced with pulsed DC power supply: the pulsed current can intermittently change the gas generation rate on the workpiece surface, avoiding the rapid aggregation of bubbles into large bubbles under continuous high current. The scouring effect of small bubbles covers the fine gaps and inner walls of blind holes in the workpiece, improving the removal effect of deep-seated oxidized oil stains. The pulse duty cycle can be set to 20%~60% as a comparative implementation variable to form a comparison with the original continuous DC scheme. If a pre-cleaning spray step is added before this process: room temperature clean water is used to perform high-pressure spraying on the workpiece after ultrasonic degreasing to pre-wash away large floating oil and dust on the workpiece surface, reducing the accumulation rate of oil stains in the electrolytic degreasing tank and extending the replacement cycle of the electrolytic tank solution; the spray water pressure can be set to a gradient variable of 0.1~0.3MPa to form multiple sets of comparative examples, thereby enriching the experimental data and technical content of the entire process.

[0025] S4. Hydrochloric acid activation impregnation: Immerse the workpiece in hydrochloric acid with a mass fraction of 15%~25% for 1~2 minutes, and then perform S2 multi-stage countercurrent water washing. After undergoing two alkaline treatment processes—ultrasonic degreasing and anodic electrolytic degreasing—the workpiece is transferred from the electrolytic cell to the water washing tank. During this process, the copper metal substrate rapidly forms a dense, thin oxide film upon contact with air and moisture, covering the entire surface of the workpiece. When nickel metal deposits on this oxide film, it only forms a physical adsorption, failing to establish a strong metallurgical bond. This leads to defects such as blistering and peeling of the coating, and also reduces the overall wear resistance of the coating. A 15%–25% hydrochloric acid solution can chemically react with the copper oxide and cuprous oxide on the copper surface, dissolving and removing the entire oxide film, exposing a clean, unoxidized pure copper substrate, providing a suitable bonding surface for subsequent nickel plating deposition.

[0026] Immersion time should be controlled between 1 and 2 minutes: If immersion time is less than 1 minute, the oxide film in shielded areas such as workpiece holes and the inner sides of bends cannot be completely dissolved, leaving a localized oxide isolation layer; if immersion time exceeds 2 minutes, hydrochloric acid will continue to corrode the exposed copper substrate, causing a slight reduction in workpiece thickness. With continuous mass production, this will lead to workpiece dimensional deviations exceeding product tolerances. After immersion, high-concentration hydrochloric acid will remain on the workpiece surface and inside crevices. If directly sent to the electroplating process, the acidic hydrochloric acid will continuously consume the boric acid buffer component in the plating solution, continuously lowering the overall pH value and disrupting the stability of the nano-nickel plating solution. Therefore, after immersion, the workpiece is transferred to an S2 multi-stage countercurrent water rinse, relying on gradient dilution to remove surface acid residue and reduce the amount of acidic medium carried into the electroplating tank.

[0027] In the embodiments, three sets of different hydrochloric acid concentration gradients and two sets of soaking time gradients can be set up to carry out control experiments, forming multiple sets of comparative implementation data; at the same time, a comparison scheme of replacing the activating agent can be added to enrich the experimental dimensions.

[0028] The first set of gradient variables is the mass fraction of hydrochloric acid, with three concentrations of 15%, 20%, and 25% set, and a uniform immersion time of 1.5 minutes (the midpoint of the range). The integrity of the oxide film removal and the degree of corrosion on the copper substrate are observed under different concentrations. 15% hydrochloric acid is suitable for newly processed workpieces with thin oxide films, 25% hydrochloric acid is used for workpieces that have been stored for a long time and have severe surface oxidation, and 20% is the general production concentration. The second set of gradient variables is the immersion time, using 20% ​​standard hydrochloric acid, immersing for 1 minute and 2 minutes respectively, detecting the oxidation residue in the workpiece's bending gaps and deep holes, and statistically analyzing the difference in substrate thickness before and after treatment. Additionally, a control example can be set up, using dilute sulfuric acid of the same concentration to completely replace the hydrochloric acid in this process for activation, comparing the corrosion rate and oxide film dissolution efficiency of the two acids on the copper substrate. This visually demonstrates the adaptability advantage of using 15%~25% hydrochloric acid for short-time immersion, making the entire process example more complete and the data support more sufficient.

[0029] S5. Copper polishing treatment, followed by S2 multi-stage counter-current water washing. After stamping, cutting, and bending, copper and red copper workpieces retain stamping marks, micro-pits, micro-burrs, and metal scratches from the forming process on their surfaces. This unevenness alters the distribution of the nickel plating thickness, resulting in thicker plating in recessed areas and thinner plating in raised areas. During subsequent assembly and use, the raised areas will preferentially bear the frictional wear of insertion and removal, accelerating plating wear and shortening product lifespan. Simultaneously, the uneven surface reduces the effective contact area between the workpiece and the mating conductive components, decreasing the stability of conductive transmission.

[0030] The copper polishing process relies on the synergistic effect of a polishing solution containing micro-abrasive particles and organic acids on the copper substrate. The organic acids in the solution create a weak and uniform etching effect on the copper surface, while the abrasive particles continuously rub the workpiece surface, eliminating various microscopic uneven structures and reducing the surface height differences between different areas. This results in a smoother overall surface, providing a foundation for the subsequent uniform deposition of a nickel plating layer. During the polishing process, the polishing solution, detached fine metal debris, and abrasive particles adhere to the workpiece's surface, bends, and the inner walls of blind holes, forming a solid residue layer. This residue cannot be completely removed from the workpiece by natural dripping. Therefore, after all polishing operations are completed, the workpiece needs to undergo a multi-stage countercurrent water washing step (S2). This step uses gradient dilution water to remove most of the suspended polishing residue from the workpiece surface, reducing the total amount of solid impurities carried into subsequent processes.

[0031] In this embodiment, after copper polishing in step S5, a pure water spray rinsing process is added to remove polishing residue from the workpiece surface and prevent polishing impurities from contaminating the nano-nickel electroplating tank.

[0032] The S2 multi-stage countercurrent water wash relies solely on static immersion of the workpiece and natural overflow of water to complete the cleaning process. The water flow has a relatively weak impact force, only able to remove large, loosely attached particles from the surface of the workpiece. Tiny abrasive particles and waxy polishing paste residue stuck in the workpiece's microscopic crevices and deep blind holes are difficult for the water flow to remove and will remain within the workpiece's crevices. The pure water spray rinsing process, combined with high-pressure pure water nozzles, continuously sprays high-speed pure water in all directions onto the workpiece. The water flow can directly penetrate areas that conventional water washing cannot reach, such as workpiece crevices, blind holes, and bends, impacting and removing small polishing solid residues stuck inside the crevices. The residues then flow directly into the matching sedimentation tank with the sprayed water, achieving solid-liquid separation.

[0033] If the pure water spray rinsing process is omitted and the workpiece is treated solely with conventional multi-stage countercurrent water washing, the polishing and grinding particles and organic wax residues remaining inside the crevices will flow into the S8 alloy nano-nickel electroplating tank along with the workpiece. Solid grinding particles, once inside the plating solution, will remain suspended within the system and adsorb onto the workpiece's plating surface during electroplating, forming dot-like raised impurities and increasing the number of pits and pinholes on the plating surface. Organic wax residues, floating on the plating solution surface, will coat localized areas of the workpiece when it is immersed in the solution, preventing nickel ions from depositing in those areas and causing localized plating defects and incomplete plating. The continuous introduction of polishing impurities will shorten the stable service life of the nano-nickel plating solution, requiring frequent filtration and cleaning of the electroplating tank and replacement of the entire solution, increasing material and labor consumption. Adding a pure water spray rinsing process reduces the total amount of polishing impurities brought into the electroplating tank by the workpiece, decreasing the frequency of plating solution maintenance.

[0034] S6, Acidic Degreasing: Treat the workpiece with an acidic degreasing solution at 40~50℃ for 1~2 minutes, and then perform S2 multi-stage countercurrent water washing. After the workpiece undergoes S5 copper polishing, the polishing paste and lubricating wax used in the polishing process remain in hidden areas such as bends, crevices, deep blind holes, and minute pits. These waxy and mineral oil contaminants are chemically stable. The hydrochloric acid used in the previous S4 step can only dissolve the metal oxide layer and cannot decompose organic oil stains. Conventional overflow rinsing can only remove loose impurities on the workpiece surface and is insufficient to remove the oil film stuck inside the crevices. The continuous adhesion of oil stains to the copper substrate surface will form an isolation layer, making it difficult for nickel ions to form a stable bond with the copper substrate during the electroplating stage. This ultimately results in significant local differences in the thickness of the plating layer, making the plating layer easy to peel off in whole pieces after external friction.

[0035] The acidic degreasing system contains both an acidic medium and emulsifying dispersion components. When the system temperature is maintained between 40 and 50°C, the molecular motion speed of the emulsifying aids increases, thereby improving the contact reaction efficiency with waxes and mineral oils. Organic oil stains can be gradually dispersed and dissolved in the solution. When the ambient temperature is below 40°C, the activity of the aids is weaker, and the decomposition process of oil stains inside the hidden structures of the workpiece slows down, leaving a small amount of oil film after treatment. When the ambient temperature is above 50°C, the volatilization rate of acidic substances in the solution accelerates, and the effective components of the solution are continuously depleted, requiring frequent replenishment of the agent to maintain the treatment effect.

[0036] A soaking time of 1-2 minutes is suitable for the production needs of conventional red copper and purple copper parts. If the soaking time is less than 1 minute, the wax oil inside the workpiece, such as deep holes and the inner sides of bends, which are not easily exposed to the solution, cannot be fully emulsified and decomposed. If the soaking time exceeds 2 minutes, the acidic medium in the solution will continue to slowly corrode the exposed copper substrate, causing changes in the microscopic smoothness of the workpiece surface, which is not conducive to the uniform deposition of the subsequent plating layer. After the workpiece leaves the acidic degreasing tank, a certain amount of acidic solution containing emulsifying agents will adhere to the surface and crevices. If it is directly sent to the S7 sulfuric acid activation process, the agent carried by the workpiece will dilute the sulfuric acid in the activation tank, reducing the dissolving ability of the oxide film. Therefore, after this process, the workpiece needs to be sent to the S2 multi-stage countercurrent water wash, relying on the gradient water flow to gradually dilute and rinse away the residual agent adhering to the workpiece surface, reducing the fluctuation of the tank performance caused by the agent being carried across processes.

[0037] S7. Sulfuric acid activation: Immerse the workpiece in 5%~10% sulfuric acid for 1~2 minutes, and then perform S2 multi-stage countercurrent water washing. During the S6 acid degreasing and S2 water rinsing transfer process, the clean copper substrate rapidly forms a very thin oxide film upon contact with air and moisture. This oxide film prevents nickel ions from depositing on the substrate surface, causing blistering and peeling of the plating layer. A 5%~10% (by mass) dilute sulfuric acid reacts with the oxides on the copper surface, dissolving and removing the surface oxide film to expose the metal substrate. Immersion time (label 5: 1~2 minutes) is crucial; insufficient time will result in incomplete dissolution of the oxide film in the shielded areas; exceeding 2 minutes will cause the dilute sulfuric acid to continuously corrode the copper substrate, leading to a slight reduction in workpiece size. The dilute sulfuric acid solution can adhere to the crevices of the workpiece, and direct entry into the electroplating bath will disrupt the acid-base balance of the plating solution. Therefore, after immersion, the workpiece is transferred to an S2 multi-stage counter-current water rinse to reduce the total amount of acid carried by the workpiece.

[0038] In the embodiments, after the hydrochloric acid activation impregnation in step S4 and the sulfuric acid activation in step S7 are completed, at least two countercurrent water washing processes are set.

[0039] A single-level water washing tank can only dilute the free acid on the surface of the workpiece. The acid retained in the gaps and blind holes of the workpiece cannot be fully removed. After a small amount of acid is continuously introduced into the electroplating tank, it will continuously consume the boric acid buffer in the plating solution, causing the pH of the plating solution to continue to decrease and increasing the frequency of plating solution maintenance.

[0040] Two or more counter-current water washing tanks form a gradient dilution system. The workpiece first enters the pre-washing tank with a higher acid concentration to rinse away most of the surface acid, and then enters the final water washing tank which is replenished with fresh water to clean the residual acidic medium deep in the crevices. This greatly reduces the total amount of acid brought into the electroplating tank and extends the stable service life of the nano nickel plating solution.

[0041] S4 uses high-concentration hydrochloric acid and S7 uses dilute sulfuric acid. Both types of acidic media will have a negative impact on the electroplating solution system. The two activation processes are equipped with multi-stage countercurrent water washing, which can simultaneously control the amount of the two types of acidic solutions carried, reduce the fluctuation range of the plating solution composition, and reduce the number of operations for adding, filtering and cleaning the electroplating solution.

[0042] S8, Alloy Nano Nickel Electroplating: Electroplating is performed using a special nano nickel plating solution. The temperature of the plating solution is controlled at 50~55℃, the pH value at 4.2~4.4, and the plating voltage at 3~5V. The plating solution is circulated and filtered throughout the electroplating process. After the electroplating is completed, S2 multi-stage countercurrent water washing is performed. This process is the core step in coating formation. After a series of previous treatments, the workpiece surface is clean, free of oxidation and oil, and has the basic conditions for coating deposition. The workpiece is immersed in a special nano-nickel plating solution, and an external DC power supply is connected to create an electric field. Under the action of the electric field, nickel ions in the plating solution migrate to the surface of the workpiece and gradually deposit to form a continuous metal coating. At the same time, nano-rare additives in the plating solution are embedded into the coating structure along with the nickel ions.

[0043] The plating bath temperature should be maintained at 50~55℃: when the temperature is below 50℃, the migration rate of nickel ions decreases, the coating deposition efficiency decreases, and the production cycle is extended; when the temperature is above 55℃, the decomposition rate of the boric acid buffer component in the plating bath accelerates, the pH value of the plating bath is prone to large fluctuations, and the evaporation of the plating bath increases, and the rate of reagent consumption increases.

[0044] The pH value of the plating solution should be stable between 4.2 and 4.4. If the pH is below 4.2, the concentration of hydrogen ions in the plating solution will be too high, and hydrogen gas will be released on the surface of the workpiece, making the plating layer prone to pinholes and pitting defects. If the pH is above 4.4, nickel ions in the plating solution will easily combine with hydroxide ions to form nickel hydroxide precipitate, resulting in the loss of effective components of the plating solution and the appearance of rough particles on the surface of the plating layer.

[0045] Electroplating voltage 3~5V: If the voltage is below 3V, the nickel deposition rate is too low and the mass production efficiency decreases; if the voltage is above 5V, the growth rate of the coating grains is accelerated, the grain size becomes larger, the coating hardness decreases, and the internal stress of the coating increases, making it easy to crack when bent.

[0046] The entire process utilizes a circulating filtration system: The density of the rare nano-additive powder added to the plating solution is greater than that of the solution itself. When left to stand, it will settle to the bottom of the tank, resulting in uneven powder content between the upper and lower layers. The circulating filtration equipment continuously draws plating solution from the bottom of the tank and returns it to the upper part of the tank through the filtration pipeline, driving continuous flow throughout the entire plating solution. This ensures that the nano-powder is evenly suspended and dispersed in all areas of the plating solution, guaranteeing uniform contact of the nano-components with the workpiece during electroplating.

[0047] After electroplating, the workpiece surface adsorbs a large amount of plating solution components. Direct drying will cause the plating solution to crystallize and precipitate, affecting the appearance and performance of the coating. Therefore, after electroplating, the workpiece is transferred to S2 multi-stage countercurrent water washing to recover and dilute the plating solution adhering to the workpiece surface, reduce material loss, and provide a clean surface for subsequent coating protection processes.

[0048] In the embodiment, a nickel plating layer with a thickness of 16 μm was obtained by electroplating in step S8, and the average Vickers hardness of the plating layer could reach 493.4 HV; when uniformly electroplating a 6 μm plating layer, the amount of nano rare additives was positively correlated with the hardness of the plating layer and negatively correlated with the flexibility of the plating layer.

[0049] The coating thickness will change the hardness test results and internal stress distribution. When the coating thickness is 16μm, there are more layers of nanoparticles inside the coating, and the hard particles have a more significant effect on hindering grain slip. The average hardness of multiple sampling tests can reach 493.4HV. When the coating thickness is controlled at 6μm, the overall coating thickness is thin, the total amount of nanoparticles is small, and the hardness benchmark value is lower than that of the thick coating.

[0050] Under the condition of fixed coating thickness, as the amount of nano-rare additives added to the plating solution gradually increases, the number of hard particles in the coating per unit volume increases simultaneously, and the coating hardness increases accordingly. Hard particles will interrupt the continuous structure of metal grains, and when the coating is bent, the crack propagation speed will accelerate, and the flexibility will decrease accordingly. The two show an inverse relationship.

[0051] Meanwhile, in step S8, the electroplating process continuously operates the circulating filtration system to ensure that the nano-rare additives in the plating solution are evenly dispersed, thus preventing the nanoparticles from settling and agglomerating, which would cause uneven coating hardness.

[0052] The density of the nano-rare additive powder is greater than that of the electroplating solution. When the plating solution is static, the powder will continuously settle to the bottom of the tank. The powder content is low in the upper layer of the plating solution and high in the lower layer. The circulating filtration equipment continuously draws the plating solution from the bottom of the tank and returns it to the upper part of the plating tank through the filtration pipeline, which drives the continuous flow of the entire plating solution. The powder is suspended and dispersed in various areas of the plating solution with the water flow.

[0053] If the filtration system stops operating, powder agglomerates and deposits at the bottom of the tank. The content of nano-components in the plating solution that the workpiece comes into contact with during electroplating is insufficient, and there are significant differences in the distribution of hard particles inside the coating. The hardness test values ​​of different areas of the same workpiece deviate more, and the hardness fluctuation range between batches of workpieces increases.

[0054] S9. Coating protection treatment, followed by S2 multi-stage counter-current water washing after protection is completed; After the S8 alloy nano-nickel electroplating and washing process, the newly deposited nano-nickel coating has high surface chemical activity, with numerous active sites in the intergranular spaces of the coating surface. When exposed to the workshop air environment, it easily adsorbs impurities such as moisture, dust, and acidic gases from the air. During the batch transfer, storage, and subsequent assembly of the workpieces, the nickel coating will continue to undergo oxidation, resulting in surface discoloration, loss of gloss, and localized oxidation spots. This not only affects the uniformity of the coating's appearance but also alters the surface conductivity and wear resistance, reducing the storage period and operational stability of the finished workpieces.

[0055] This process involves a protective coating treatment that generates a uniform, thin protective film on the surface of the nano-nickel coating. This film covers the entire exposed surface of the coating, preventing direct contact between the nickel coating and air, moisture, and corrosive impurities. This inhibits the continuous oxidation reaction of the coating, reduces the probability of discoloration and oxidation failure, and stabilizes the coating's hardness, toughness, conductivity, and wear resistance.

[0056] After the protective immersion treatment, a large amount of free protective agent concentrate and residual agent film will adhere to the surface of the workpiece's flat surfaces, crevices, and blind holes. If it directly enters the drying process, the residual agent will precipitate white agent crystals and water stains under high temperature, adhering to the coating surface and causing appearance defects in the finished product. At the same time, the accumulation of excess agent will slightly cover the surface structure of the coating, indirectly affecting the bonding effect of subsequent silver plating assembly processes. Therefore, after the protective process is completed, the workpiece needs to be transferred to the S2 multi-stage countercurrent water washing process, where gradient dilution water flow washes and dilutes the residual protective agent on the workpiece surface, removing excess agent residue.

[0057] Step S9 involves immersion in a water-soluble nickel protective agent for coating protection, followed by thorough rinsing. The drying stage is controlled at 60-80℃ to avoid high-temperature damage to the coating's hardness and toughness.

[0058] This process uses a water-soluble nickel protective agent as the protective medium. Compared to oil-based protective agents, the solute components of the water-soluble protective agent are completely soluble in water, resulting in uniform penetration and a thin, uniform film thickness that does not form a thick, accumulated layer on the nickel plating surface. Furthermore, the water-soluble protective film does not possess insulating properties, thus it will not interfere with subsequent processes such as silver plating and conductive assembly, making it suitable for the subsequent processing and use requirements of conductive copper components in AI servers.

[0059] Immersion treatment allows the protective agent to fully wet the entire surface of the workpiece, including irregular structures such as bends, micropores, and grooves. This ensures that the protective film adheres to the entire workpiece surface, preventing gaps in protection in localized areas and improving the uniformity of the protective effect for batches of workpieces.

[0060] The water washing operation after protective treatment must be thorough. Multi-stage countercurrent water washing can gradually dilute the trace protective agent residues left in the gaps and micro-textures of the workpiece, reduce the accumulation of agent residues, and avoid appearance defects such as fogging, whitening, and color difference of the coating after drying. At the same time, it ensures that the protective film only retains the effective film layer that is firmly bonded to the surface of the coating, and removes free and ineffective agent components.

[0061] After washing, the workpiece enters the drying process, with the drying temperature strictly controlled within the range of 60-80℃. The nano-nickel coating contains an intergranular structure filled with rare nano-additives, making its internal stress state and grain arrangement highly sensitive to temperature changes. When the drying temperature exceeds 80℃, the high-temperature environment promotes thermal growth of the nickel grains within the coating, altering the original refined grain structure. Simultaneously, it disrupts the bonding between the nanoparticles and the nickel matrix, leading to a decrease in the overall hardness of the coating. Furthermore, the high temperature increases residual stress within the coating, making stress concentration points prone to cracking during bending, thus reducing the coating's bending resistance and structural stability.

[0062] When the drying temperature is below 60℃, the residual moisture adhering to the workpiece surface evaporates slowly, significantly increasing drying time and reducing overall production efficiency. Furthermore, trace amounts of moisture can easily remain deep within the workpiece's crevices; prolonged moisture retention can induce slow oxidation and rusting of the coating, affecting the stability of the finished product during storage. A temperature range of 60~80℃ can rapidly dry the moisture on the workpiece surface while maintaining the internal grain structure and nanofiller distribution of the coating, stabilizing its hardness and bending toughness.

[0063] S10. Drying process to obtain the finished workpiece.

[0064] The special nano nickel plating solution contains the following components at the following concentrations: nickel ions 80g / L, nickel chloride 20g / L, boric acid 40g / L, comprehensive organic additives 100ml / L, and nano rare additives 5~10g / L.

[0065] After the preceding multi-stage counter-current water washing process, the workpiece's surface, including its planes, micro-textures, crevices, and blind holes, is covered with free moisture and trace amounts of residual aqueous solution. Natural air drying at room temperature cannot completely remove the moisture trapped within the hidden structures. Prolonged moisture adhering to the surface of the nano-nickel plating will continuously induce slow oxidation and discoloration of the plating, while also leaving water stains, affecting the workpiece's appearance consistency and plating stability. This process uses a drying treatment, heating and drying the entire workpiece to thoroughly remove residual moisture from the surface and crevices, halting the subsequent slow oxidation process of the plating, and stabilizing the surface condition and mechanical properties of the plating.

[0066] Based on the aforementioned S9 process requirements, the drying temperature in this step is maintained in a low-temperature range of 60~80℃. Under this temperature condition, the internal grain arrangement structure of the nano-nickel coating will not be altered, the dispersion state of the nano-additives within the coating will not be damaged, and the hardness and bending toughness of the cured coating can be preserved. After drying, the coating structure, mechanical properties, and appearance of the workpiece tend to stabilize, completing the entire electroplating process and obtaining finished red copper and purple copper workpieces that can be directly used for assembly, inspection, and storage.

[0067] In the above, a special nano-nickel plating solution is used to complete the deposition of the alloy nickel layer. The concentrations of each component are matched and work synergistically to form a nano-nickel plating layer with high hardness and high toughness. The specific functions and parameter limiting principles of each component are as follows.

[0068] The nickel ion concentration in the plating bath is set at 80 g / L. Nickel ions are the core metallic raw material for coating deposition and are the main component of the nickel coating matrix. When the nickel ion concentration is below 80 g / L, the content of depositable metallic components in the plating bath is insufficient, the migration and deposition rate of nickel ions during the electroplating process decreases, the coating thickness is thinner under the same electroplating time, and the mass production deposition efficiency decreases. When the nickel ion concentration is above 80 g / L, the solute saturation of the plating bath increases, and nickel salt crystallization precipitation is likely to occur in the tank. The crystal particles are prone to clogging the circulation filter pipes, and at the same time, it will increase the surface roughness of the coating and increase the coating particle defects.

[0069] The nickel chloride content in the plating bath is 20 g / L. Nickel chloride provides stable chloride ions to the plating bath, aiding in the normal dissolution and activation of the nickel plate on the electroplated anode and mitigating anode passivation. Maintaining a stable dissolved state at the anode continuously replenishes the nickel ions consumed by the plating bath, keeping the nickel ion concentration in the plating bath stable and reducing fluctuations in nickel ion concentration during the electroplating process. If the chloride ion content is too low, the anode is prone to passivation and blackening; insufficient nickel ion replenishment results in uneven coating thickness. If the chloride ion content is too high, it increases the internal stress of the coating and reduces its bending resistance.

[0070] The plating bath contains 40 g / L of boric acid. Boric acid acts as a buffer component, neutralizing the hydrogen ions continuously generated during the electroplating reaction and suppressing rapid pH fluctuations. The electroplating process continuously consumes this buffer; without a stable boric acid system, the pH of the plating bath would continuously decrease, leading to defects such as pinholes and peeling in the plating layer. This concentration of boric acid is suitable for the temperature and voltage range of this process, maintaining the pH of the plating bath within the reasonable range of 4.2–4.4 over a long period, reducing the frequency of plating bath adjustments and extending the service life of the plating bath.

[0071] The comprehensive organic additive dosage in the plating bath is 100 ml / L. This type of additive has grain refinement and dispersion assistance functions. During the electroplating deposition process, it can be adsorbed at the nickel grain growth interface, limiting abnormal nickel grain growth, reducing the grain size of the coating, reducing the overall internal stress of the coating, and improving the flatness and bending performance of the coating. At the same time, this additive can form a dispersion isolation layer on the surface of nanoparticles, reducing nanoparticle agglomeration and helping the rare nanoparticles to be uniformly suspended in the plating bath system, providing a basic guarantee for the uniformity of coating performance.

[0072] The amount of rare nano-additives added to the plating solution is 5~10g / L. This component is the core functional component for improving the hardness of the coating. The nano-sized powder can fill the gaps between nickel plating grains, increase the sliding resistance between grains, and effectively improve the overall Vickers hardness of the coating. The addition amount can be set in a range, allowing the process parameters to be adjusted according to the application scenario of the workpiece. When the addition amount is in the range of 5g / L, the coating toughness retention is higher, which is suitable for workpieces that need to be repeatedly bent and assembled. When the addition amount is in the range of 10g / L, the coating hardness is further improved, which is suitable for copper parts of AI servers with high wear resistance and low bending conditions.

[0073] Nano-rare additives are the core functional components for altering the mechanical properties of nickel plating. After being incorporated into the intergranular spaces of the nickel plating grains, these nanoparticles can change the grain growth state and internal structure of the nickel layer, thus having a regular influence on the hardness and bending flexibility of the plating. Under the production conditions defined by the standard electroplating process parameters, fixed plating solution components, and uniform plating thickness specified in this invention, the mechanical properties of the plating will exhibit a stable gradient change with the increase or decrease of the amount of nano-rare additives added. The dosage of the additives can be adjusted to suit the operating conditions of different workpieces.

[0074] When the amount of rare nano-additives added to the plating solution is set to 5 g / L, the concentration of nano-powder dispersion in the plating solution is moderate. During the deposition process, an appropriate amount of nano-powder uniformly fills the intergranular spaces of nickel metal, effectively increasing the grain slip resistance, inhibiting the deformation of the plating layer under stress, and improving the overall hardness of the plating layer. Batch electroplating testing verified that the Vickers hardness of the nickel plating layer prepared under this addition condition can be stably maintained at 470 HV or higher, showing a significant increase in hardness compared to conventional ordinary nickel plating layers, which can meet the wear-resistant requirements of conventional server copper components.

[0075] At an addition level of 5 g / L, the proportion of hard nanoparticles inside the coating is relatively low, which does not significantly disrupt the continuous microstructure of nickel metal grains, and the coating still retains sufficient metallic ductility. When the workpiece is subjected to a 90° reciprocating bending test, the coating can deform synchronously with the copper substrate and can withstand 6 consecutive 90° reciprocating bending operations without producing visible cracks, peeling, or flaking defects on the coating surface. It is suitable for processing red copper and purple copper workpieces that require multiple bending and assembly deformation.

[0076] When the amount of rare nano-additives added to the plating bath is increased to 10 g / L, the number of suspended nano-hard powders per unit volume of the plating bath increases significantly. The density of embedded hard particles during the plating deposition process continues to rise, resulting in more complete filling of intergranular spaces and further enhancing the deformation resistance of the internal structure of the plating. The hindering effect of hard particles on grain slip continues to strengthen, leading to a further increase in the overall hardness of the plating. The Vickers hardness of the prepared nickel plating can reach over 500 HV, further improving the wear resistance of the plating and making it suitable for high-wear, high-load applications.

[0077] As the amount of rare nano-additives continues to increase, the proportion of non-metallic hard particles inside the coating continues to increase. The originally continuous grain structure of nickel metal is divided and blocked by a large number of hard particles, and the overall metallic ductility of the coating gradually decreases while its brittleness relatively increases. Under the same 90° reciprocating bending test conditions, the coating's ability to withstand deformation stress decreases, and stress tends to concentrate at the interface between the particles and the metal matrix, generating microcracks. This reduces the number of 90° reciprocating bends the workpiece can withstand to 3 times. After exceeding this number of bends, crack defects will appear in the coating, affecting the reliability of the workpiece.

[0078] Based on the above performance variation patterns, the additive dosage can be adjusted according to the actual use requirements of the product to achieve a suitable balance between coating hardness and bending flexibility. This can meet the hardness requirements of high wear resistance conditions and also take into account the toughness requirements of bending assembly conditions, thereby improving the adaptability and versatility of the process for mass production.

[0079] The rare nanoparticles used in this process are nanoscale alloy rare powders, with the overall particle size controlled within the range of 10~100nm. This particle size range is suitable for this nano-nickel electroplating system. If the powder particle size is less than 10nm, the specific surface area of ​​the powder is too large, and the surface activity is too high. During the static and flowing process of the plating solution, it is very easy to spontaneously agglomerate and accumulate, and cannot disperse independently. The agglomerated fine particles will cause local stress concentration in the coating, reducing the overall stability of the coating.

[0080] If the powder particle size is greater than 100nm, the particle size is too large and cannot be embedded in the micro-grain gaps of the nickel plating layer. It can only adhere to the surface of the plating layer or be mixed in the interior of the plating layer, which will form structural defects inside the plating layer, increase the brittleness of the plating layer, significantly reduce the bending resistance of the workpiece, and at the same time cause the surface roughness and flatness of the plating layer to decrease.

[0081] This process limits the powder particle size to 10~100nm. Powder particles of this size can match the growth gap size of nickel grains and can be uniformly filled into the interior of the coating grain structure during the nickel ion deposition process. This has a refining and constraining effect on the growth of nickel grains, improves the overall density of the coating structure, increases the grain slip resistance, and thus improves the overall hardness and wear resistance of the coating.

[0082] When the nano-alloy rare powder is added into the plating solution alone, there is a tendency of adsorption and agglomeration between particles, and it is difficult for the powder to be uniformly suspended in the plating solution system for a long time. When the powder is compounded with the comprehensive organic additive matched with the process, molecules of the comprehensive organic additive can adsorb on the surface layer of nano-powder particles, forming an isolated hydration layer on the outer side of the particles. The isolated hydration layer can weaken the adsorption force between nano-powder particles, reduce the probability of particle agglomeration and sedimentation, enable the nano-powder to be stably dispersed and suspended inside the overall plating solution system, and make the content of nano-particles contacted by various regions of the workpiece tend to be consistent during electroplating.

[0083] The uniformly dispersed nano-powder is evenly distributed inside the plating layer, which can overall improve the hardness of the plating layer. Meanwhile, no particle accumulation and concentration occurs in local positions, which can retain the inherent metal ductility characteristic of the nickel plating layer, weaken the negative impact of hard particles on the toughness of the plating layer, and maintain the basic bending toughness of the nickel layer while improving the hardness of the plating layer, so as to adapt to the assembly and bending working conditions of copper parts after electroplating.

[0084] The above shows and describes the basic principle, main features and advantages of the present invention. For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments.

Claims

1. A high-hardness alloy nano-nickel electroplating process, characterized in that, Applicable to the machining of red copper / pure copper workpieces, including the following steps: S1. Ultrasonic degreasing: Place the workpiece in a degreasing solution at 50~60℃ and ultrasonically treat it for 10~15 minutes. S2. Multi-stage counter-current water washing: The workpiece is rinsed using a multi-stage counter-current clean water method; S3, Anodic Electrolytic Degreasing: Electrolytic degreasing at a controlled temperature of 50~60℃ for 3~5 minutes, followed by S2 multi-stage countercurrent water washing; S4. Hydrochloric acid activation impregnation: Immerse the workpiece in hydrochloric acid with a mass fraction of 15%~25% for 1~2 minutes, and then perform S2 multi-stage countercurrent water washing. S5. Copper polishing treatment, followed by S2 multi-stage counter-current water washing. S6, Acidic Degreasing: Treat the workpiece with an acidic degreasing solution at 40~50℃ for 1~2 minutes, and then perform S2 multi-stage countercurrent water washing. S7. Sulfuric acid activation: Immerse the workpiece in 5%~10% sulfuric acid for 1~2 minutes, and then perform S2 multi-stage countercurrent water washing. S8, Alloy Nano Nickel Electroplating: Electroplating is performed using a special nano nickel plating solution. The temperature of the plating solution is controlled at 50~55℃, the pH value at 4.2~4.4, and the plating voltage at 3~5V. The plating solution is circulated and filtered throughout the electroplating process. After the electroplating is completed, S2 multi-stage countercurrent water washing is performed. S9. Coating protection treatment, followed by S2 multi-stage counter-current water washing after protection is completed; S10. Drying process to obtain the finished workpiece.

2. The high-hardness alloy nano-nickel electroplating process according to claim 1, characterized in that: The special nano nickel plating solution contains the following components at the following concentrations: nickel ions 80g / L, nickel chloride 20g / L, boric acid 40g / L, comprehensive organic additives 100ml / L, and nano rare additives 5~10g / L.

3. The high-hardness alloy nano-nickel electroplating process according to claim 1, characterized in that: When the amount of nano-rare additives added is 5g / L, the Vickers hardness of the resulting nickel coating is stable at ≥470HV, and the workpiece can withstand 6 rounds of 90° bending without cracking. When the amount of nano-rare additives added is increased to 10g / L, the Vickers hardness of the coating can reach more than 500HV, and the number of rounds of 90° bending that the workpiece can withstand is reduced to 3.

4. The high-hardness alloy nano-nickel electroplating process according to claim 1, characterized in that: A nickel plating layer with a thickness of 16 μm was obtained by electroplating in step S8, and the average Vickers hardness of the plating layer reached 493.4 HV. When electroplating a 6 μm plating layer, the amount of nano rare additives was positively correlated with the hardness of the plating layer and negatively correlated with the flexibility of the plating layer.

5. The high-hardness alloy nano-nickel electroplating process according to claim 4, characterized in that: In step S8, the electroplating process continuously operates the circulating filtration system to ensure that the nano-rare additives in the plating solution are evenly dispersed, thus preventing the nanoparticles from settling and agglomerating, which would cause uneven coating hardness.

6. The high-hardness alloy nano-nickel electroplating process according to claim 1, characterized in that: After the hydrochloric acid activation and impregnation process in step S4 and the sulfuric acid activation process in step S7 are completed, at least two countercurrent water washing processes are set up.

7. The high-hardness alloy nano-nickel electroplating process according to claim 1, characterized in that: After copper polishing in step S5, a pure water spray rinsing process is added to remove polishing residue from the workpiece surface and prevent polishing impurities from contaminating the nano-nickel electroplating tank.

8. The high-hardness alloy nano-nickel electroplating process according to claim 1, characterized in that: Step S9 involves immersion in a water-soluble nickel protective agent for coating protection, followed by thorough rinsing. The drying stage is controlled at 60-80℃ to avoid high-temperature damage to the coating's hardness and toughness.

9. The high-hardness alloy nano-nickel electroplating process according to claim 7, characterized in that: The nano-rare additives are made of nano-alloy rare powders with a particle size controlled between 10 and 100 nm. When these powders are combined with comprehensive organic additives, they can be uniformly dispersed in the plating solution system, simultaneously improving the hardness of the plating layer while retaining the bending toughness of the nickel layer.